Forty Years of Budgetary Slack Research: A Systematic Literature Review and Future Agenda - Ida Ayu Ratih Manuari; Ni Made Dwi Ratnadi; Eka Ardhani Sisdyani; I Gusti Ayu Eka Damayanthi (AIBPM Publisher, 2025)
This study reviews the evolution of budgetary slack research over the past four decades, reflecting its growing importance in management accounting and governance contexts. The objective is to synthesize trends, theoretical developments, variables, methods, and publication patterns, while identifying research gaps and future directions. Using a Systematic Literature Review (SLR) approach, this study analyzes 111 Scopus-indexed articles published between 1985 and 2025 through thematic manual coding and descriptive qualitative analysis. The results indicate a shift from dominant reliance on agency theory and economic motivations toward more multidimensional perspectives incorporating behavioral, psychological, social, and institutional factors, with increasing attention to public sector settings and developing countries. Despite this progress, gaps remain in integrating interdisciplinary frameworks and contextual variables, particularly political influences on budgeting behavior. This study concludes that future research should adopt multi-theoretical approaches, including frameworks such as Political Economy of Accounting, to better capture the complexity of budgetary slack. The findings provide practical implications for policymakers and practitioners in designing more effective budgeting systems, performance evaluation, and accountability mechanisms, while offering a structured foundation for advancing scholarly work in this field.